Effect of different chemical treatments on the settleability of palm oil mill effluent - Hassan, Mohd Ali; Phang, Lai Yee; Abdul Rahman, Nor'aini; Shirai, Yoshihito; Ariff, Arbakariya; Abdul Karim, Mohamed Ismail (Universiti Putra Malaysia Press, 2001)
The effect of alum and ferric chloride on the settleability of suspended solids in raw palm oil mill effluent (POME) was compared with that of natural zeolite and calcium carbonate. This work forms part of our overall research on minimal discharge technology in the overall management of POME. The results showed that all the flocculants could effectively reduce more than 80% of the suspended solids but only 40-50% of the COD. The settled volume after 3-7 hours was generally within 35-50% of the original mixture. The best settleability in increasing order were at 3 giL ferric chloride, 11 giL alum, 10 giL zeolite and 20 giL calcium carbonate. The fastest settling rate was obtained with 20 giL calcium carbonate, where settling was almost completed within 2 hours as compared to more than 20 hours for raw POME. The dosage of zeolite was comparable to the traditional coagulants. As for calcium carbonate, although the dosage was higher, subsequent disposal or utilisation of the metalfree sludge solids fits well with our minimal discharge system for POME.